PENGAWASAN PETUGAS OPERASIONAL KEBERSIHAN KOTA PEKANBARU (Studi Kasus Keselamatan Tenaga Kerja di Kecamatan Tampan) - Sundariana, Gea; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The Operational hygiene officer is a person who is a charge to sweeping the road,containing garbage,cleaning up the canal and the road culverts and also treating plants along the side walk and city park. Bassed on operational standars at Departement of Hygiene in Pekanbaru, there are still same problem which became a phenomenom that has mot implemented the surveillance of the operational hygiene officer safety on HR.Subrantas streets,Tampan sub-District which is accident in the street while sweeping and the officer that doesn’t wear their uniform and work attribute well.This research aims to knowing and analysing the survelillance of the operational hygiene officer in pekanbaru city (study case officer’s safety in sub-District Tampan). This research use descriptive qualitative method with collecting data technique such like interviews,observation and literature study.The result of this research are the opperational hygiene officers surveillance by Departement of Hygiene doesn’t running as well this is because the disobediance of the operational hygiene officer against the rules that have been set the factor that influence the operational hygiene officers surveillance are the lack of human resource from Departement of Hygiene,in this matter,the foreman and also lack of awareners of the operational hygiene officers of their safety while work.Keyword: surveillance,Operational Hygiene Officer